Training Program on the Fabrication and Maintenance of Rapid Ice Cube Production Systems Utilizing Split Air Conditioner Compressors for the Youth of Reuleut Timu Village - Muhammad; Reza Putra; Muhammad; Nurul Islami; Muhammad Gazza; Dailami; Muhammad Habibi; Muhammad Ihsan (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
The demand for ice cubes among the community and vendors around the Universitas Malikussaleh campus has increased in tandem with the university's expansion. Reuleut Timu, a village situated within the university's vicinity, possesses the potential to develop ice cube production and distribution enterprises, particularly catering to beverage and juice vendors managed by local residents and students. This condition presents an opportunity for the youth of Reuleut Timu to generate income and stimulate the growth of the creative economy. The production process involves utilizing repurposed air conditioner (AC) compressors. This assembly is characterized by its ease of construction, energy efficiency, and the ability to produce ice cubes in a relatively short duration of 3 to 4 hours. The objective of this training is to provide knowledge and information to the local youth regarding rapid ice-making equipment, with the aim of establishing village-owned or private enterprises. The methodology employed included training in equipment assembly and maintenance, followed by a one-month internship for the participants. The results of the training indicated high levels of participant enthusiasm, with attendees gaining proficiency in the construction and maintenance of rapid ice-making machines. Community support for this initiative was substantial, evidenced by orders placed for the equipment to be used for business purposes. Participants intend to utilize this equipment as a village-based enterprise to serve as a source of revenue, fulfilling the significant local demand for beverage-related businesses.